Clinical differences between outpatients with and without internet addiction and emotional disorders: a prospective naturalistic outcome study - Zhou, Jiaqi; Rosmarin, David H.; Pirutinsky, Steven (Frontiers in Psychiatry, 2024)
Background/Objective: as internet use becomes increasingly ingrained in contemporary society, internet addiction (IA) has emerged as a global public health concern. There is ongoing debate regarding whether IA represents a distinct psychological disorder or a secondary manifestation of other existing disorders.This study aimed to examine the pathological relationship between IA and emotional disorders (ED).Method: this study compared pre-treatment characteristics and treatment process of three groups of patients (N=1292) at an outpatient clinic: IA only, ED only, and comorbidity of IA and ED. Results: the IA only group differed from the other groups by reporting the highest levels of life satisfaction, adaptive emotion regulation, as well as risk behavior urges at intake. In addition, the IA only group displayed the lowest level of depressive and anxiety symptoms throughout the treatment.Conclusions: our findings contribute to a better understanding of the discreteness of IA as a potential psychological disorder and inform more effective treatment strategies for IA and its comorbid conditions.